Analisis Tingkat Kenyamanan Di Kota Manado Dan Wilayah Penyangganya Berdasarkan Indeks Thi (Temperature Humidity Index) - WIDIYANTO, SOFIAN; KURNIA, WENAS GANDA (Megasains, 2020)
As one of the provinces that is the center of the economy in Eastern Indonesia, North Sulawesi is a destination for migrants, with many migrants coming from year to year, making the North Sulawesi region increasingly crowded, especially in Manado and its supporting regencies / cities. The rapid growth of development in various sectors can lead to a reduction in green open space and can also cause social problems and environmental problems that can cause inconvenience of an area for its inhabitants. The preparation of this comfort index was made to find out how much the comfort level was in several districts / cities in North Sulawesi using the Temperature Humidity Index (THI) method. The data used in this study are daily air temperature and humidity data for 2008 - 2017 at the Sam Ratulangi Meteorological Station in Manado, Bitung Meteorological Station, North Minahasa Climatology Station and Tondano Minahasa Geophysical post. The THI index in Manado, Bitung, North Minahasa and Minahasa generally only a portion of the population (28.15%) of cities felt comfortable and in the category of Most Comfortable with an average of 59.97%. and the Uncomfortable category occurred at 11.87%. The lowest level of comfort felt by residents of the City of Bitung while feeling comfortable in the open space felt by residents of Minahasa Regency. The increasing trend of the THI index occurs in almost all cities except Bitung City with the largest rate experienced by the city of Manado.